Implikasi Konsep Pendidikan Seumur Hidup - Nabila Khairani; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Every human being is born in a state of not knowing anything, but he is gifted with a tool that he can use to gain knowledge. That tool is reason, with reason, humans can think and contemplate everything. The presence of reason is also directly controlled by an important device called the heart. It is the heart that helps the mind in digesting and practicing various kinds of knowledge. This research is a qualitative research with data obtained through literary sources (library research), namely literature studies through library research. that lifelong education is very important for us to apply in our daily lives. There is no stopping word in studying, because science and technology continues to develop dynamically and progressively. When we stop seeking knowledge, it is almost certain that we will be left behind by the times.